Genomics and nitrogen metabolic characteristics of a novel heterotrophic nitrifying-aerobic denitrifying bacterium Acinetobacter oleivorans AHP123. (May 2023) - Zhou, Xiangqun; Wang, Yuanli; Tan, Xin; Sheng, Yequan; Li, Yanbin; Zhang, Qin; Xu, Jialu; Shi, Zhengsheng
Graphical abstract: Highlights: A novel HNAD bacteria, Acinetobacter oleivorans AHP123, was isolated. Strain AHP123 can effectively remove ammonia nitrogen at 45 °C. The ammonia nitrogen of 95.92 mg/L could remove 97.93% in 24 h by the strain. Strain AHP123 may have incomplete HNAD and nitrogen assimilation pathways. Nitrogen assimilation is the main nitrogen removal path of strain AHP123. Abstract: A novel aerobic strain of Acinetobacter oleivorans AHP123 was isolated from activated sludge, which could conduct heterotrophic nitrification and denitrification simultaneously. This strain has excellent NH4 + -N removal ability, with 97.93% removal rate at 24-hour. To identify the metabolic pathways of this novel strain, genes of gam, glnA, gdhA, gltB, nirB, nasA, nar, nor, glnK and amt were detected by genome analysis. Through RT-qPCR, it was found that the expression of key genes confirmed two possible ways of nitrogen removal in strain AHP123: nitrogen assimilation and heterotrophic nitrification aerobic denitrification (HNAD). However, the absence of some common HNAD genes ( amo, nap and nos ) suggested that strain AHP123 might have a different HNAD pathway from other HNAD bacteria. Nitrogen balance analysis revealed that strain AHP123 assimilated most of the external nitrogen sources into intracellular nitrogen.